Testing Financial Constraint Hypothesis of Investment in NEPSE Listed Companies - Subedi, Kapil Dev (Saptagandaki Journal, 2023)
This study aims to test financing constraints of Nepalese firms and its impact on investment behavior by controlling the accelerator effect. It divides the firms into Financially Constrained (FC) and Unconstrained (UC) group using discriminant analysis and uses Econometric Model to analyze investment cashflow sensitivities (ICFS) of firms. The data comprised the accounting observations (n=256) obtained from the annual reports of 16 non-financial companies listed in Nepal Stock Exchange Ltd. Results show that financially constrained firm exhibit higher cashflow sensitivity indicating significant influence of financing constraints on Nepalese firm's investment behavior. It documents the evidence of financial market inefficiency, urging for policy prescriptions to address these constraints and spur investment and growth.